A method for preparing high dispersibility glass fiber chopped strands
Patent Information
- Application Number
- CN202611287280.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明的目的是为了解决现有技术中玻璃纤维短切丝分散性差、易团聚、与基体结合力弱等问题,提供一种高分散性玻璃纤维短切丝制备方法,实现玻璃纤维短切丝的高分散性、高相容性和高力学性能
[0020] Compared with existing technologies, the technical solution provided by this invention improves the melt flowability of glass raw materials from the source by combining nano-dispersants and anti-agglomeration agents, reducing the tendency of agglomeration during fiber forming. It employs a combination of vibration stirring and inert gas protection to remove bubbles and impurities, ensuring the uniformity of continuous filaments and preventing agglomeration after stubble cutting due to uneven filament distribution. Pre-stubble cutting removes impurities and broken fibers, followed by fine stubble cutting, combined with low-temperature cooling airflow, reducing fiber damage and adhesion during stubble cutting and ensuring uniform stubble length. The combination of initial ultrasonic dispersion and secondary airflow dispersion thoroughly breaks down small agglomerates while avoiding excessive ultrasonic damage to the fibers. This not only solves the core problems of poor dispersibility and easy agglomeration of chopped glass fibers in existing technologies but also achieves simultaneous improvement in dispersibility and mechanical properties.
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass fiber preparation technology, and more specifically to a method for preparing highly dispersible glass fiber chopped strands. Background Technology
[0002] Chopped glass fiber filaments are widely used in composite material reinforcement, filter materials, and thermal insulation due to their excellent properties such as high strength, corrosion resistance, good insulation, and lightweight. Dispersibility is one of the core performance indicators of chopped glass fiber filaments, and its uniformity directly affects the mechanical properties, molding quality, and product stability of composite materials. Poor dispersion of chopped glass fiber filaments can easily lead to agglomeration, resulting in stress concentration within the composite material, decreased mechanical strength, reduced toughness, and even affecting the appearance and performance of the product.
[0003] Currently, existing methods for preparing chopped glass fiber filaments mainly involve a three-step process: melt drawing, chopping, and surface treatment. However, in existing technologies, to improve dispersibility, methods such as using a single surface modifier, adjusting the chopped length, or optimizing the drawing process are often employed. A single surface modifier cannot simultaneously address both the compatibility between the glass fiber and the matrix material and the anti-agglomeration ability between fibers, resulting in limited modification effects. Traditional chopping processes are mostly single-pass mechanical chopping, leading to uneven filament length distribution and easy fiber breakage and surface damage during the chopping process, further exacerbating agglomeration. Some methods improve dispersibility by increasing the amount of dispersant, but this increases production costs and may affect the bonding force between the glass fiber and the matrix, reducing the overall performance of the composite material. Summary of the Invention
[0004] The purpose of this invention is to solve the problems of poor dispersibility, easy agglomeration, and weak bonding with the matrix of chopped glass fibers in the prior art, and to provide a method for preparing highly dispersible chopped glass fibers, so as to achieve high dispersibility, high compatibility and high mechanical properties of chopped glass fibers.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows:
[0006] A method for preparing highly dispersible glass fiber chopped strands includes the following steps:
[0007] Step 1: Select alkali-free glass raw materials, including 55-65 parts of quartz sand, 15-25 parts of feldspar, 5-10 parts of boric acid, 3-8 parts of dolomite, 2-5 parts of alumina, and 1-3 parts of calcium oxide by weight. Add 0.5-2 parts of nano-dispersant and 0.3-1 parts of anti-agglomeration agent, mix evenly, and then put into a high-temperature calcining furnace for calcination. After cooling to room temperature, crush to obtain modified glass raw materials.
[0008] Step 2: The modified glass raw material is fed into a melting furnace and melted at 1500-1600℃. The temperature is maintained for 2-3 hours, and vibration and stirring are performed during the process. Then, the molten glass is passed through a drawing stencil. Inert protective gas is introduced during the drawing process. After drawing, continuous glass fiber filaments are obtained.
[0009] Step 3: The obtained continuous glass fiber filaments are pre-cut, and then the pre-cut glass fibers are sent into a fine cutting device. During the cutting process, cooling airflow is used for real-time cooling to obtain primary glass fiber chopped filaments.
[0010] Step 4: Place the primary glass fiber chopped strands into a modification tank, add a composite surface modifier, and stir at 40-50℃ for 30-60 minutes. After modification, send the mixture into a centrifugal dehydrator to obtain modified glass fiber chopped strands after dehydration.
[0011] Step 5: First, the obtained modified glass fiber chopped strands are fed into an ultrasonic dispersion device for initial dispersion, then into an airflow dispersion device for secondary dispersion, and finally into a drying oven to obtain highly dispersible glass fiber chopped strands.
[0012] Preferably, in step one, the nano-dispersing agent is a compound of nano-silica and nano-alumina, with a mass ratio of 3:1 to 2:1, and the particle size of the nano-dispersing agent is 50-100 nm. The anti-agglomeration agent is a compound of calcium stearate and polyethylene glycol, with a mass ratio of 2:1 to 1:1, and the particle size of the anti-agglomeration agent is 1-5 μm.
[0013] Preferably, in step two, a high-frequency vibration device is used for vibration stirring. The vibration direction of the high-frequency vibration device is perpendicular to the flow direction of the molten glass, and the viscosity of the molten glass during vibration stirring is 1000-1500 mPa·s.
[0014] Preferably, in step two, the aperture of the wire drawing stencil is 8-12 μm, and the wire drawing speed is 800-1200 m / min.
[0015] Preferably, in step two, the inert protective gas is a mixture of nitrogen and argon with a volume ratio of 4:1 to 3:1, and the inert protective gas flow rate is 0.5-1 m³ / h.
[0016] Preferably, in step three, the pre-cut length is 10-15 mm, the pre-cut speed is 50-80 m / min, the fine cut length is 3-8 mm, and the cut speed is 100-150 m / min.
[0017] Preferably, in step three, the cooling airflow is a mixture of dry air and liquid nitrogen, with a volume ratio of 5:1 to 4:1, a cooling airflow temperature of -5 to 0°C, and a flow rate of 1 to 2 m / s.
[0018] Preferably, the composite surface modifier in step four is composed of the following components in parts by weight: 3-5 parts of silane coupling agent, 1-2 parts of titanate coupling agent, 2-4 parts of waterborne polyurethane emulsion, 20-30 parts of ethanol, and 60-70 parts of deionized water. The silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, and the titanate coupling agent is isopropyltristearatetoxytitanate.
[0019] Preferably, in step five, the ultrasonic dispersion device uses intermittent ultrasonication, pausing for 1 minute after every 5 minutes of ultrasonication. A guide plate is installed inside the airflow dispersion device, with the guide plate at an angle of 30-45° to the airflow direction. Hot air circulation is used for drying during the drying process, with a hot air velocity of 0.5-1 m / s. Drying is carried out at 80-100℃ for 1-2 hours, with a moisture content ≤0.5%.
[0020] Compared with existing technologies, the technical solution provided by this invention improves the melt flowability of glass raw materials from the source by combining nano-dispersants and anti-agglomeration agents, reducing the tendency of agglomeration during fiber forming. It employs a combination of vibration stirring and inert gas protection to remove bubbles and impurities, ensuring the uniformity of continuous filaments and preventing agglomeration after stubble cutting due to uneven filament distribution. Pre-stubble cutting removes impurities and broken fibers, followed by fine stubble cutting, combined with low-temperature cooling airflow, reducing fiber damage and adhesion during stubble cutting and ensuring uniform stubble length. The combination of initial ultrasonic dispersion and secondary airflow dispersion thoroughly breaks down small agglomerates while avoiding excessive ultrasonic damage to the fibers. This not only solves the core problems of poor dispersibility and easy agglomeration of chopped glass fibers in existing technologies but also achieves simultaneous improvement in dispersibility and mechanical properties. Detailed Implementation
[0021] It is readily understood that, based on the technical solution of this invention, those skilled in the art can propose various interchangeable structural methods and implementations without altering the essential spirit of the invention. Therefore, the following specific embodiments are merely illustrative examples of the technical solution of this invention and should not be considered as the entirety of the invention or as limitations or restrictions on the technical solution of this invention.
[0022] As a specific embodiment of the method for preparing highly dispersible glass fiber chopped filaments provided by the present invention, the method includes selecting alkali-free glass raw materials, which, by weight, include 55-65 parts of quartz sand, 15-25 parts of feldspar, 5-10 parts of boric acid, 3-8 parts of dolomite, 2-5 parts of alumina, and 1-3 parts of calcium oxide. Then, 0.5-2 parts of nano-dispersant and 0.3-1 parts of anti-agglomeration agent are added, and the mixture is thoroughly mixed before being fed into a high-temperature calcining furnace at 800-900°C. The material is calcined at 00℃ for 2-3 hours, cooled to room temperature, and then pulverized to a particle size of 100-200 mesh to obtain modified glass raw material. The nano-dispersant is a compound of nano-silica and nano-alumina in a mass ratio of 3:1-2:1, and the anti-agglomeration agent is a compound of calcium stearate and polyethylene glycol in a mass ratio of 2:1-1:1. The particle size of the nano-dispersant is 50-100 nm, and the particle size of the anti-agglomeration agent is 1-5 μm.
[0023] The modified glass raw material is fed into a melting furnace and melted at 1500-1600℃ for 2-3 hours. During this period, a high-frequency vibration device is used for vibration stirring at a frequency of 20-30Hz and an amplitude of 5-10μm. The vibration direction of the high-frequency vibration device is perpendicular to the flow direction of the molten glass. The viscosity of the molten glass is checked every 30 minutes during the vibration stirring process and controlled to be 1000-1500mPa·s. Bubbles and impurities in the molten glass are removed. The molten glass is then passed through a drawing die with an aperture of 8-12μm and a drawing speed of 800-1200m / min. An inert protective gas, a mixture of nitrogen and argon with a volume ratio of 4:1-3:1, is introduced during the drawing process. After drawing, continuous glass fiber filaments are obtained. The inert protective gas flow rate is 0.5-1m³ / h to prevent oxidation of the glass fiber surface during the drawing process.
[0024] The obtained continuous glass fiber filaments are first pre-chopped to a length of 10-15 mm at a speed of 50-80 m / min to remove broken fibers and impurities. Pre-chopping uses a rotary cutter with a speed of 1500-2000 r / min and a cutter gap of 0.3-0.5 mm. The pre-chopped glass fibers are then fed into a fine chopping device, where a length of 3-8 mm is chopped at a speed of 100-150 m / min. The fine chopping device uses diamond-coated cutters with a cutter gap of 0.1-0.2 mm and a speed of 3000-4000 r / min. During the chopping process, real-time cooling is achieved using a cooling airflow at a temperature of -5 to 0℃ and a flow rate of 1-2 m / s. This yields primary chopped glass fiber filaments. The cooling airflow is a mixture of dry air and liquid nitrogen with a volume ratio of 5:1-4:1 to ensure no damage to the fiber surface during the chopping process.
[0025] A composite surface modifier is prepared, comprising the following components in parts by weight: 3-5 parts silane coupling agent, 1-2 parts titanate coupling agent, 2-4 parts waterborne polyurethane emulsion, 20-30 parts ethanol, and 60-70 parts deionized water. The silane coupling agent is γ-aminopropyltriethoxysilane (KH-550) or γ-glycidyl etheroxypropyltrimethoxysilane (KH-560), and the titanate coupling agent is isopropyltristearate titanate (NDZ-101). The waterborne... The polyurethane emulsion has a solid content of 30-40% and a viscosity of 50-100 mPa·s (25℃). Primary glass fiber chopped filaments are placed in a modification tank, and a composite surface modifier is added at a bath ratio of 1:10-1:15. The modification is carried out by stirring at 40-50℃ for 30-60 min at a stirring speed of 50-80 r / min. After modification, the mixture is sent to a centrifugal dehydrator at a dehydration speed of 2000-3000 r / min for 5-10 min to obtain modified glass fiber chopped filaments.
[0026] The modified glass fiber chopped strands were first fed into an ultrasonic dispersion device with an ultrasonic power of 100-150W, an ultrasonic time of 10-20 minutes, and an ultrasonic frequency of 20-30kHz for initial dispersion. The ultrasonic dispersion device used intermittent ultrasonication, pausing for 1 minute every 5 minutes to avoid excessive ultrasonication that could cause fiber breakage. Subsequently, they were fed into an airflow dispersion device with an airflow velocity of 3-5 m / s and an airflow temperature of 20-30℃ for secondary dispersion to remove a small amount of agglomerates. A guide plate was installed in the airflow dispersion device at a 30-45° angle to the airflow direction to improve dispersion uniformity. Finally, the dispersed glass fiber chopped strands were sent into a drying oven and dried at 80-100℃ for 1-2 hours, controlling the moisture content to ≤0.5%. Hot air circulation drying was used during the drying process, with a hot air velocity of 0.5-1 m / s to ensure uniform drying and obtain highly dispersible glass fiber chopped strands.
[0027] It should be noted that the high-frequency vibration device, fine short-cut device, ultrasonic dispersion device, and airflow dispersion device are all existing technologies, and their specific structures will not be described in detail here.
[0028] Example 1
[0029] Alkali-free glass raw materials were selected, including 60 parts by weight of quartz sand, 20 parts of feldspar, 8 parts of boric acid, 5 parts of dolomite, 3 parts of alumina, and 2 parts of calcium oxide. One part of a nano-dispersant (nano-silica to nano-alumina mass ratio 3:1, particle size 80 nm) and 0.6 parts of an anti-agglomeration agent (calcium stearate to polyethylene glycol mass ratio 2:1, particle size 3 μm) were added. After thorough mixing, the mixture was placed in a high-temperature calcining furnace and calcined at 850℃ for 2.5 h. After cooling to room temperature, the mixture was pulverized to a particle size of 150 mesh to obtain the modified glass raw material. The purity of all raw materials met the following requirements: quartz sand ≥ 99.5%, feldspar ≥ 98%, boric acid ≥ 99%, and the remaining raw materials ≥ 98.5%.
[0030] The modified glass raw material was fed into a melting furnace and melted at 1550℃ for 2.5 hours. During this period, a high-frequency vibration device (vibration frequency 25Hz, amplitude 8μm) was used for vibration and stirring, with the vibration direction perpendicular to the flow direction of the molten glass. The viscosity of the molten glass was measured every 30 minutes and controlled to be 1200 mPa·s. Then, the molten glass was passed through a drawing stencil (orifice diameter 10μm) at a drawing speed of 1000 m / min, while an inert protective gas (nitrogen to argon volume ratio 4:1, flow rate 0.8 m³ / h) was introduced. After drawing, continuous glass fiber filaments were obtained.
[0031] The continuous glass fiber filaments are first fed into a rotary pre-cutting device (cutter speed 1800 r / min, cutter gap 0.4 mm), with a pre-cutting length of 12 mm and a pre-cutting speed of 65 m / min to remove broken fibers and impurities. Then, they are fed into a fine cutting device (diamond-coated cutter, cutter gap 0.15 mm, cutter speed 3500 r / min), with a fine cutting length of 5 mm and a cutting speed of 120 m / min. During the cutting process, a cooling airflow (dry air to liquid nitrogen volume ratio 5:1, temperature -2℃, flow rate 1.5 m / s) is introduced to obtain primary glass fiber chopped filaments.
[0032] A composite surface modifier was prepared, comprising, by weight, 4 parts of γ-aminopropyltriethoxysilane (KH-550), 1.5 parts of isopropyltristearate titanate (NDZ-101), 3 parts of waterborne polyurethane emulsion (solid content 35%, viscosity 80 mPa·s), 25 parts of ethanol, and 66.5 parts of deionized water. Primary glass fiber chopped strands were placed in a modification tank, and the composite surface modifier was added at a bath ratio of 1:12. The modification was carried out by stirring at 45°C for 45 min at a stirring speed of 65 r / min. After modification, the strands were sent to a centrifugal dehydrator (speed 2500 r / min, time 8 min) to obtain modified glass fiber chopped strands.
[0033] Modified glass fiber chopped strands were fed into an ultrasonic dispersion device and subjected to intermittent ultrasonication (power 120W, frequency 25kHz, 1min pause after every 5min of ultrasonication, total ultrasonication time 15min) for initial dispersion. Subsequently, they were fed into an airflow dispersion device (airflow velocity 4m / s, temperature 25℃, guide plate at a 40° angle to the airflow direction) for secondary dispersion. Finally, they were sent into a drying oven and dried using hot air circulation (hot air velocity 0.8m / s, temperature 90℃) for 1.5h, with the moisture content controlled to ≤0.5%, to obtain highly dispersible glass fiber chopped strands.
[0034] The glass fiber chopped filaments prepared in this embodiment were tested and found to have a dispersion of 98.5%, an agglomeration rate of 1.5%, a length deviation of ±0.4 mm, a bonding force with the epoxy resin matrix that is 32% higher than that of the prior art, a tensile strength that is 27% higher, a moisture content of 0.4%, and no obvious agglomeration phenomenon after 3 months of storage.
[0035] Example 2
[0036] Alkali-free glass raw materials were selected, including 55 parts by weight of quartz sand, 25 parts of feldspar, 5 parts of boric acid, 8 parts of dolomite, 2 parts of alumina, and 1 part of calcium oxide. Then, 0.5 parts of nano-dispersant (nano-silica to nano-alumina mass ratio 2:1, particle size 50 nm) and 0.3 parts of anti-agglomeration agent (calcium stearate to polyethylene glycol mass ratio 1:1, particle size 1 μm) were added. After uniform mixing, the mixture was fed into a high-temperature calcining furnace and calcined at 800℃ for 3 hours. After cooling to room temperature, it was pulverized to a particle size of 100 mesh to obtain the modified glass raw material. The purity of all raw materials met the following requirements: quartz sand ≥ 99.5%, feldspar ≥ 98%, boric acid ≥ 99%, and the remaining raw materials ≥ 98.5%.
[0037] The modified glass raw material was fed into a melting furnace and melted at 1500℃ for 3 hours. During this period, a high-frequency vibration device (vibration frequency 20Hz, amplitude 5μm) was used for vibration and stirring, with the vibration direction perpendicular to the flow direction of the molten glass. The viscosity of the molten glass was measured every 30 minutes and controlled to be 1000mPa·s. Then, the molten glass was passed through a drawing stencil (orifice diameter 8μm) at a drawing speed of 800m / min, while an inert protective gas (nitrogen to argon volume ratio 3:1, flow rate 0.5m³ / h) was introduced. After drawing, continuous glass fiber filaments were obtained.
[0038] The continuous glass fiber filaments are first fed into a rotary pre-cutting device (cutter speed 1500 r / min, cutter gap 0.3 mm), with a pre-cutting length of 10 mm and a pre-cutting speed of 50 m / min to remove broken fibers and impurities. Then, they are fed into a fine cutting device (diamond-coated cutter, cutter gap 0.1 mm, cutter speed 3000 r / min), with a fine cutting length of 3 mm and a cutting speed of 100 m / min. During the cutting process, a cooling airflow (dry air to liquid nitrogen volume ratio 4:1, temperature -5℃, flow rate 1 m / s) is introduced to obtain primary glass fiber chopped filaments.
[0039] A composite surface modifier was prepared, comprising, by weight, 3 parts of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560), 1 part of isopropyltristearate titanate (NDZ-101), 2 parts of waterborne polyurethane emulsion (solid content 30%, viscosity 50 mPa·s), 20 parts of ethanol, and 74 parts of deionized water. Primary glass fiber chopped strands were placed in a modification tank, and the composite surface modifier was added at a bath ratio of 1:10. The mixture was stirred at 40°C for 30 min at a stirring speed of 50 r / min. After modification, the mixture was sent to a centrifugal dehydrator (speed 2000 r / min, time 5 min) to obtain modified glass fiber chopped strands.
[0040] Modified glass fiber chopped strands were fed into an ultrasonic dispersion device and subjected to intermittent ultrasonication (power 100W, frequency 20kHz, 1min pause every 5min, total ultrasonication time 10min) for initial dispersion. Then, they were fed into an airflow dispersion device (airflow velocity 3m / s, temperature 20℃, guide plate at a 30° angle to the airflow direction) for secondary dispersion. Finally, they were sent into a drying oven and dried with hot air circulation (hot air velocity 0.5m / s, temperature 80℃) for 2h, controlling the moisture content to ≤0.5%, to obtain highly dispersible glass fiber chopped strands.
[0041] The glass fiber chopped strands prepared in this embodiment were tested and found to have a dispersion of 98.2%, an agglomeration rate of 1.8%, a length deviation of ±0.3 mm, a bonding force with the polypropylene matrix that is 30% higher than that of the prior art, a tensile strength that is 25% higher, a moisture content of 0.3%, and no obvious agglomeration phenomenon after 3 months of storage.
[0042] Example 3
[0043] Alkali-free glass raw materials were selected, including 65 parts by weight of quartz sand, 15 parts of feldspar, 10 parts of boric acid, 3 parts of dolomite, 5 parts of alumina, and 3 parts of calcium oxide. Two parts of nano-dispersant (nano-silica to nano-alumina mass ratio 2.5:1, particle size 100nm) and one part of anti-agglomeration agent (calcium stearate to polyethylene glycol mass ratio 1.5:1, particle size 5μm) were added. After thorough mixing, the mixture was fed into a high-temperature calcining furnace and calcined at 900℃ for 2 hours. After cooling to room temperature, the mixture was pulverized to a particle size of 200 mesh to obtain the modified glass raw material. The purity of all raw materials met the following requirements: quartz sand ≥ 99.5%, feldspar ≥ 98%, boric acid ≥ 99%, and the remaining raw materials ≥ 98.5%.
[0044] The modified glass raw material was fed into a melting furnace and melted at 1600℃ for 2 hours. During this time, a high-frequency vibration device (vibration frequency 30Hz, amplitude 10μm) was used for vibration and stirring, with the vibration direction perpendicular to the flow direction of the molten glass. The viscosity of the molten glass was measured every 30 minutes and controlled to be 1500mPa·s. Then, the molten glass was passed through a drawing stencil (orifice diameter 12μm) at a drawing speed of 1200m / min, while an inert protective gas (nitrogen to argon volume ratio 3.5:1, flow rate 1m³ / h) was introduced. After drawing, continuous glass fiber filaments were obtained.
[0045] The continuous glass fiber filaments are first fed into a rotary pre-cutting device (cutter speed 2000 r / min, cutter gap 0.5 mm), with a pre-cutting length of 15 mm and a pre-cutting speed of 80 m / min to remove broken fibers and impurities. Then, they are fed into a fine cutting device (diamond-coated cutter, cutter gap 0.2 mm, cutter speed 4000 r / min), with a fine cutting length of 8 mm and a cutting speed of 150 m / min. During the cutting process, a cooling airflow (dry air to liquid nitrogen volume ratio 4.5:1, temperature 0℃, flow rate 2 m / s) is introduced to obtain primary glass fiber chopped filaments.
[0046] A composite surface modifier was prepared, comprising, by weight, 5 parts of γ-aminopropyltriethoxysilane (KH-550), 2 parts of isopropyltristearate titanate (NDZ-101), 4 parts of waterborne polyurethane emulsion (solid content 40%, viscosity 100 mPa·s), 30 parts of ethanol, and 59 parts of deionized water. Primary glass fiber chopped strands were placed in a modification tank, and the composite surface modifier was added at a bath ratio of 1:15. The modification was carried out by stirring at 50°C for 60 min at a stirring speed of 80 r / min. After modification, the strands were sent to a centrifugal dehydrator (speed 3000 r / min, time 10 min) to obtain modified glass fiber chopped strands.
[0047] Modified glass fiber chopped strands were fed into an ultrasonic dispersion device and subjected to intermittent ultrasonication (power 150W, frequency 30kHz, 1min pause every 5min, total ultrasonic time 20min) for initial dispersion. Then, they were fed into an airflow dispersion device (airflow velocity 5m / s, temperature 30℃, guide plate at a 45° angle to the airflow direction) for secondary dispersion. Finally, they were sent into a drying oven and dried with hot air circulation (hot air velocity 1m / s, temperature 100℃) for 1h, with the moisture content controlled to ≤0.5%, to obtain highly dispersible glass fiber chopped strands.
[0048] The glass fiber chopped filaments prepared in this embodiment were tested and found to have a dispersion of 98.8%, an agglomeration rate of 1.2%, a filament length deviation of ±0.5 mm, a bonding force with the nylon matrix that is 35% higher than that of the prior art, a tensile strength that is 28% higher, a moisture content of 0.4%, and no obvious agglomeration phenomenon after 3 months of storage.
[0049] Addressing the core issues of poor dispersibility and easy agglomeration of chopped glass fibers in existing technologies, this invention innovates from multiple dimensions: First, in the raw material modification stage, the combination of nano-dispersants and anti-agglomeration agents improves the melt flowability of glass raw materials from the source, reducing the tendency to agglomerate during fiber forming; Second, in the melt drawing stage, a combination of high-frequency vibration stirring and inert gas protection is used to remove bubbles and impurities, ensuring the uniformity of continuous filaments and avoiding agglomeration after chopping due to uneven filament distribution; Third, a segmented chopping process, involving pre-chopping... The process involves several key steps: First, impurities and broken fibers are removed, followed by fine shaving. Low-temperature cooling airflow reduces fiber damage and adhesion during shaving, ensuring uniform filament length. Second, a composite surface modifier combines silane coupling agents and titanate coupling agents with an aqueous polyurethane emulsion. This improves the compatibility between the glass fiber and the matrix material and forms a protective film on the fiber surface, effectively preventing fiber agglomeration. Third, a graded dispersion process combines initial ultrasonic dispersion with secondary airflow dispersion to thoroughly break down any remaining agglomerates while avoiding excessive ultrasonic damage to the fibers. These synergistic innovations not only address the core pain points of existing technologies but also achieve simultaneous improvements in dispersibility and mechanical properties. The resulting glass fiber shavings exhibit excellent dispersibility (≥98%), agglomeration rate (≤2%), and filament length deviation (≤±0.5mm). The bonding strength with the resin matrix is increased by over 30%, and the mechanical strength is increased by over 25%. Furthermore, they possess excellent corrosion resistance, insulation, and mechanical properties, have low moisture content, good storage stability, and are not prone to moisture absorption and agglomeration.
[0050] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A method for preparing highly dispersible glass fiber chopped strands, characterized in that, Includes the following steps: Step 1: Select alkali-free glass raw materials, including 55-65 parts of quartz sand, 15-25 parts of feldspar, 5-10 parts of boric acid, 3-8 parts of dolomite, 2-5 parts of alumina, and 1-3 parts of calcium oxide by weight. Add 0.5-2 parts of nano-dispersant and 0.3-1 parts of anti-agglomeration agent, mix evenly, and then put into a high-temperature calcining furnace for calcination. After cooling to room temperature, crush to obtain modified glass raw materials. Step 2: The modified glass raw material is fed into a melting furnace and melted at 1500-1600℃. The temperature is maintained for 2-3 hours, and vibration and stirring are performed during the process. Then, the molten glass is passed through a drawing stencil. Inert protective gas is introduced during the drawing process. After drawing, continuous glass fiber filaments are obtained. Step 3: The obtained continuous glass fiber filaments are pre-cut, and then the pre-cut glass fibers are sent into a fine cutting device. During the cutting process, cooling airflow is used for real-time cooling to obtain primary glass fiber chopped filaments. Step 4: Place the primary glass fiber chopped strands into a modification tank, add a composite surface modifier, and stir at 40-50℃ for 30-60 minutes. After modification, send the mixture into a centrifugal dehydrator to obtain modified glass fiber chopped strands after dehydration. Step 5: First, the obtained modified glass fiber chopped strands are fed into an ultrasonic dispersion device for initial dispersion, then into an airflow dispersion device for secondary dispersion, and finally into a drying oven to obtain highly dispersible glass fiber chopped strands.
2. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: The nano-dispersing agent mentioned in step one is a compound of nano-silica and nano-alumina, with a mass ratio of 3:1 to 2:1 and a particle size of 50-100 nm. The anti-agglomeration agent is a compound of calcium stearate and polyethylene glycol, with a mass ratio of 2:1 to 1:1 and a particle size of 1-5 μm.
3. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: In step two, a high-frequency vibration device is used for vibration stirring. The vibration direction of the high-frequency vibration device is perpendicular to the flow direction of the molten glass. During the vibration stirring process, the viscosity of the molten glass is 1000-1500 mPa·s.
4. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: The aperture of the wire drawing stencil in step two is 8-12μm, and the wire drawing speed is 800-1200m / min.
5. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, 3, or 4, characterized in that: The inert protective gas mentioned in step two is a mixture of nitrogen and argon with a volume ratio of 4:1 to 3:1, and the inert protective gas flow rate is 0.5-1 m³ / h.
6. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: In step three, the pre-cut length is 10-15mm and the pre-cut speed is 50-80m / min. The fine cut length is 3-8mm and the cut speed is 100-150m / min.
7. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: The cooling airflow in step three is a mixture of dry air and liquid nitrogen, with a volume ratio of 5:1 to 4:
1. The temperature of the cooling airflow is -5 to 0℃, and the flow rate is 1 to 2 m / s.
8. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: The composite surface modifier described in step four consists of the following components in parts by weight: 3-5 parts of silane coupling agent, 1-2 parts of titanate coupling agent, 2-4 parts of waterborne polyurethane emulsion, 20-30 parts of ethanol, and 60-70 parts of deionized water. The silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, and the titanate coupling agent is isopropyltristearatetoxytitanate.
9. The method for preparing highly dispersible glass fiber chopped strands according to claim 1, characterized in that: The ultrasonic dispersion device mentioned in step five uses intermittent ultrasound, pausing for 1 minute after every 5 minutes of ultrasound. The airflow dispersion device is equipped with a guide plate, which is at an angle of 30-45° to the airflow direction. Hot air circulation is used for drying during the drying process, with a hot air velocity of 0.5-1 m / s. The drying is carried out at 80-100℃ for 1-2 hours, and the moisture content is ≤0.5%.